Enhancement of thermoelectric efficiency of doped PCDTBT polymer films. Issue 82 (5th September 2015) - Maiz, Jon; Muñoz Rojo, Miguel; Abad, Begoña; Wilson, Adam Andrew; Nogales, Aurora; Borca-Tasciuc, Diana-Andra; Borca-Tasciuc, Theodorian; Martín-González, Marisol
<x xml:space="preserve">Abstract</x> PCDTBT films doped with FeCl3 present a large power factor of 24 μW m−1 K−2 at 150 °C and a thermal conductivity of 1 W m−1 K−1 for the same film. This improvement is mainly achieved by up to 9 orders of magnitude increased in the electric conduction.